2018
DOI: 10.2147/hiv.s138638
|View full text |Cite
|
Sign up to set email alerts
|

Dietary diversity and associated factors among HIV positive adults attending antiretroviral therapy clinics at Hiwot Fana and Dilchora Hospitals, eastern Ethiopia

Abstract: BackgroundNutritional care is considered a crucial component of comprehensive care for people living with HIV/AIDS (PLWHA), particularly in resource-limited settings where malnutrition and food insecurity are endemic problems, and low quality monotonous diets are the norm. The findings of this study provide baseline information on dietary diversity and related factors for health care providers so that they will be able to improve nutritional care and support activity. Therefore, the aim of this study was to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 19 publications
2
39
1
Order By: Relevance
“…Food insecurity and poor nutritional status causes lower CD4 cell counts, poor adherence to ART, decreased viral suppression, and increase morbidity and mortality. It can also accelerate the development of opportunistic infections and result in the progress of AIDS-related illnesses among People Living with HIV AIDS [8].…”
Section: Introductionmentioning
confidence: 99%
“…Food insecurity and poor nutritional status causes lower CD4 cell counts, poor adherence to ART, decreased viral suppression, and increase morbidity and mortality. It can also accelerate the development of opportunistic infections and result in the progress of AIDS-related illnesses among People Living with HIV AIDS [8].…”
Section: Introductionmentioning
confidence: 99%
“…These problems are due to insufficient food consumption and altered metabolic situations, aggravating the reduced balance of energy and nutrients in patients even when they are treated with antiretroviral therapy (ART). 7,8 Nutrition is a significant component of inclusive care for HIV-positive patients and is particularly so in resource-limited settings where malnutrition and food insecurity are endemic. 9 Dietary management of HIV-positive patients is key to supporting their capacity to continue participating in the workforce and contributing to socio-economic growth.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the mean dietary diversity score (DDS) was 4, which is below the minimum [27]. While other study showed that 28.7% of HIV/AIDS patients had low DDS [9]. Thus, the aforementioned factor and study area context makes ART clients vulnerable to malnutrition; even if, there is signi cant improvement after ART enrollment.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, it is among one of the clinical targets to be achieved through ART follow up period. The study from eastern Ethiopia showed that 28.7% of HIV/AIDS patients had low Dietary diversity score [9].…”
Section: Introductionmentioning
confidence: 99%